First records of leucistic House Sparrows ("Passer domesticus") in the Andaman and Nicobar Islands, India - Gokulakrishnan, G.; Sivaperuman, C.; Narayana, B. Laxmi (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The House Sparrow "Passer domesticus" is a small member of the family Passeridae and commonly found in many parts of the world (Ali and Ripley 2001). Unusual plumage colouration has been described in detail in this species (Van Grouw 2012) but the proportion and distribution of abnormally coloured individuals is not well known for many parts of the species` range. Here we describe the first records of leucistic House Sparrows in the Andaman and Nicobar Islands, India.
Keywords: wróblowe; ornitologia